Risk Aversion in Agnatic Inheritance: Theoretical Analysis of the Case of One or More Female Heirs Without Brothers - Mohamed EL GRAA (Al-Infaq Jurnal Ekonomi Islam, 2026)
This article analyzes inheritance practices in Morocco, particularly the rule of Taasib, which favors indirect male heirs. Increasingly contested, this rule is prompting many families to adopt alternative mechanisms such as hiba (donation), sadaqa (charitable donation) or fictitious sale, in order to protect direct heirs, particularly daughters without brothers. The study shows that inheritance choices vary according to education and social background. It highlights the need for legal and religious reform to reconcile tradition and equity in response to contemporary social and economic challenges.